ADDRESSING DISPARITIES IN MULTISECTORAL EDUCATION: LEARNING FROM AN INTERNATIONAL LITERATURE REVIEW - Loso Judijanto; Aslan Aslan (Indonesian Journal of Education (INJOE), 2025)
This article explores ways to address disparities in education through a multisectoral approach, drawing on a review of international literature. Disparities in education, which are influenced by socio-economic, geographical, gender and physical ability factors, require holistic solutions that involve various sectors such as health, economy and society. The review emphasises the importance of policies that not only focus on infrastructure and curriculum but also provide social and financial support for disadvantaged groups. In addition, sustainable and data-driven programme planning is needed to identify the groups most in need of interventions and the types of interventions that are most effective. By adopting this approach, education policy can be more dynamic and responsive to challenges, potentially significantly reducing educational disparities.